Assessment of community nutrition program performance through data validation in the state of Chhattisgarh - Sinha, Ashish; Dixit, Srishti; Soni, G. P.; Pradhan, Somen Kumar; Naqwi, Sarwat (International Journal Of Community Medicine And Public Health, 2018)
Background: In India data shows that every 3rd child is underweight. There is a similar situation in Chhattisgarh with 37% children underweight. Women and Child Development Department initiated Nawa Jatan (“new care”), a state specific community based intervention by targeting undernourished children for Six month. Strategy of validation by ‘External technical support group’ can be an eye opener for strategic tactical and operational intervention to validate the data of ICDS scheme at field level. Methods: By systematic random sampling methodology, Out of all targeted 2462 Gram Panchayats (GPs) 246 (i.e. 10%) was included in the survey. One day hands-on demonstration cum training for survey teams mixed with interns, postgraduate and volunteers were organized. Data collection done in pretested proforma. Results: A total of 7155 children distributed in surveyed Gram Panchayats across 27 districts were covered. About 9.1% (651 out of 7155) children showed gap in reporting as they were reported normal grade of nutrition. Out of all children covered for actual field validation. There was 9.84% disagreement in weight recording in the state. Our analysis reveals 9 districts fall in poor performing districts, followed by below average performing 8 districts and average performing 10 districts. Conclusions: There is wide gap in recorded result as normal children against the observation which was actually in the field level. In addition, there is significant proportion of disagreement of weight records when compared with actual weighing. Above observations might be possibly due to poor monitoring and supervision of weighing activity at the field level.